Functional Characterization of GhACX3 Gene Reveals Its Significant Role in Enhancing Drought and Salt Stress Tolerance in Cotton - Shiraku, Margaret L.; Magwanga, Richard Odongo; Cai, Xiaoyan; Kirungu, Joy Nyangasi; Xu, Yanchao; Mehari, Teame Gereziher; Hou, Yuqing; Wang, Yuhong; Agong, Stephen Gaya; Peng, Renhai; Wang, Kunbo; Zhou, Zhongli; et al. (Frontiers in Plant Science, 2021)
The acyl-coenzyme A oxidase 3 (ACX3) gene involved in the β-oxidation pathway plays a critical role in plant growth and development as well as stress response. Earlier on, studies focused primarily on the role of β-oxidation limited to fatty acid breakdown. However, ACX3 peroxisomal β-oxidation pathways result in a downstream cascade of events that act as a transduction of biochemical and physiological responses to stress. A role that is yet to be studied extensively. In this study, we identified 20, 18, 22, 23, 20, 11, and 9 proteins in Gossypium hirsutum, G. barbadense, G. tomentosum, G. mustelinum, G. darwinii, G. arboretum, and G. raimondii genomes, respectively. The tetraploid cotton genome had protein ranging between 18 and 22, while diploids had between 9 and 11. After analyzing the gene family evolution or selection pressure, we found that this gene family undergoes purely segmental duplication both in diploids and tetraploids. W-Box (WRKY-binding site), ABRE, CAAT–Box, TATA-box, MYB, MBS, LTR, TGACG, and CGTCA-motif are abiotic stress cis-regulatory elements identified in this gene family. All these are the binding sites for abiotic stress transcription factors, indicating that this gene is essential. Genes found in G. hirsutum showed a clear response to drought and salinity stress, with higher expression under drought and salt stress, particularly in the leaf and root, according to expression analysis. We selected Gh_DO1GO186, one of the highly expressed genes, for functional characterization. We functionally characterized the GhACX3 gene through overexpression and virus-induced gene silencing (VIGS). Overexpression of this gene enhanced tolerance under stress, which was exhibited by the germination assay. The overexpressed seed growth rate was faster relative to control under drought and salt stress conditions. The survival rate was also higher in overexpressed plants relative to control plants under stress. In contrast, the silencing of the GhACX3 gene in cotton plants resulted in plants showing the stress susceptibility phenotype and reduced root length compared to control. Biochemical analysis also demonstrated that GhACX3-silenced plants experienced oxidative stress while the overexpressed plants did not. This study has revealed the importance of the ACX3 family during stress tolerance and can breed stress-resilient cultivar.